A clinical analysis and literature review of eleven cases with primary pulmonary angiosarcoma - Tao Luan; Jianqing Hao; Yingying Gu; Ping He; Yijia Li; Liqiang Wang; Haiyi Deng; Wenhui Guan; Xinqing Lin; Xiaohong Xie; Yu Deng; Shuaiying Wang; et al. (BMC Cancer)
Abstract Objective The aim of this study is to explore the clinicopathological features, radiographic manifestations, treatment options, and prognosis of primary pulmonary angiosarcoma (PPAS). Method We summarized and analyzed the clinical data of 11 patients with primary pulmonary angiosarcoma treated at the First Affiliated Hospital of Guangzhou Medical University between January 2018 and January 2024. A retrospective analysis was conducted in conjunction with a review of the relevant literature. Results Among the 11 cases, the primary symptoms were nonspecific respiratory issues, with chest pain, cough, and shortness of breath being the most common. Initial diagnosis was correct in only 2 cases, while the remaining 9 cases were misdiagnosed as other conditions, such as lung nodules, infections, or pulmonary embolism. All patients were ultimately diagnosed via pathology, with CD31 and CD34 showing a high positivity rate of 60%. Of the 11 patients, 9 have died, and 2 remain alive. The average survival period was 13.2 months.Based on the number of lesions, PPAS was categorized into three types: solitary, multiple, and invasive pulmonary artery. The average survival period for the solitary type (2 cases) was 15.5 months, for the multiple type (5 cases) was 6.6 months, and for the pulmonary artery type (4 cases) was 20.5 months. Among the 3 patients who underwent surgery, the median overall survival (OS) was 23.0 months, whereas for the 8 non-surgical patients, the median OS was 9.7 months. Conclusion Primary pulmonary angiosarcoma is a rare, highly aggressive vascular malignancy characterized by nonspecific clinical symptoms and a tendency for metastasis and pulmonary artery embolism. Currently, no effective treatment exists, and the overall prognosis is poor.